Electrodiagnosis of Guillain-Barre syndrome in the International GBS Outcome Study: Differences in methods and reference values. (June 2022) - Arends, Samuel; Drenthen, Judith; van den Bergh, Peter; Franssen, Hessel; Hadden, Robert D.M.; Islam, Badrul; Kuwabara, Satoshi; Reisin, Ricardo C.; Shahrizaila, Nortina; Amino, Hiroshi; Antonini, Giovanni; Attarian, Shahram; et al.
Highlights: Electrodiagnosis (EDx) methodology is heterogeneous across the regions and often differed from the methodology of the applied reference values. EDx reference values vary globally among IGOS centers. Future studies in Guillain-Barré syndrome patients should use a standardized EDx protocol. Abstract: Objective: To describe the heterogeneity of electrodiagnostic (EDx) studies in Guillain-Barré syndrome (GBS) patients collected as part of the International GBS Outcome Study (IGOS). Methods: Prospectively collected clinical and EDx data were available in 957 IGOS patients from 115 centers. Only the first EDx study was included in the current analysis. Results: Median timing of the EDx study was 7 days (interquartile range 4–11) from symptom onset. Methodology varied between centers, countries and regions. Reference values from the responding 103 centers were derived locally in 49%, from publications in 37% and from a combination of these in the remaining 15%. Amplitude measurement in the EDx studies (baseline-to-peak or peak-to-peak) differed from the way this was done in the reference values, in 22% of motor and 39% of sensory conduction. There was marked variability in both motor and sensory reference values, although only a few outliers accounted for this. Conclusions: Our study showed extensive variation in the clinical practice of EDx in GBS patients among IGOS centers across the regions. Significance: Besides EDx variation in GBS patients participating in IGOS, this diversity is likely to be present in other neuromuscular disorders and centers. This underlines the need for standardization of EDx in future multinational GBS studies.